Formação docente: investigando possibilidades e desafios de uma disciplina EaD - Anzolin Filho, Edisson (2021)
Technological advances have been promoting changes in the educational context and expanding the possibilities of access to education. In this sense, teacher training through distance education courses has been expanded, making it possible to overcome barriers such as geographic location and time, which are often the impeding factors in teacher training. From this angle, this dissertation, developed in the line of research on Teacher Education for Professional and Technological Education of the Academic Master's Degree in Professional and Technological Education, aims to investigate the potential and challenges of offering a discipline of Fundamentals of Chemistry in distance education, in training of Biology teachers. The research is based on the methodology of participatory action research, targeting 29 students from an undergraduate course in Biological Sciences. The course is offered in distance learning mode, with Moodle as a virtual environment, the activities of this environment being an instrument of data collection, as well as two questionnaires of the survey type, made available at the beginning and at the end of the discipline. The results obtained make it possible to infer that the offer of distance training is still a challenge, both for teachers and students, requiring new attitudes and a different didactic conception.